Use of SRPK1 inhibitors for the treatment of Diabetic Retinopathy - Malhi, Naseeb (2021)
Microvascular damage results from ischaemia-driven production of pro- angiogenic vascular endothelial growth factor (VEGF). Proximally spliced VEGF is upregulated in the ischemic diabetic retina and has been implicated as the principal driver of the pathological growth and leakage of blood vessels during diabetic retinopathy (DR). Serine-Arginine Rich protein kinase-1 (SRPK1) regulates splicing of VEGF, and inhibition of this kinase with small molecular weight inhibitors has been shown to inhibit choroidal neovascularization (CNV) in mice by decreasing pro-angiogenic and increasing anti-angiogenic VEGF isoforms. These isoforms have previously been described to inhibit increased vascular permeability with protective effects against DR-induced pathology. SRPK1 inhibitors such as SPHINX31 may therefore switch splicing in DR and prevent increased vascular permeability.